CHARACTERISTICS OF MARKETING IN PROFESIONAL SERVICES DELIVERED BY THE HEALTHCARE SYSTEM - Carmen Gabriela SECARA; Flaviu MEGHISAN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Equilibrium position of a competitive market must necessarily be an „pareto optimal”: with every transaction made, people get rich without anyone else to deplete. If there is no increasing income - economies of scale or proportion - in the production system, then each „pareto optimal” condition is a competitive equilibrium position, depending on the distribution of purchasing power. Where there are concerns about income distribution and hence of goods and services between individuals, the state can interfere by changing this algorithm of purchasing power distribution, within the economy. On the other hand, if some individuals are reluctant to risk (theory contradicted by the existence of gambling), then providing insurances is incumbent on mutually beneficial exchanges, because people are willing to pay for the convenience of not having to worry about the future events that may affect their existence. Another problem of the insurance field is that of ”moral hazard": since signing an insurance contract, the insured is no longer trying as hard to prevent accidents against which they have been insured, therefore the likelihood of occurrence for such accidents increases.